(3GdJbSje hGdJHjjf aj Mce CehGd GdeSJZQbjfs - (3CHh RcQjG jMji Hf eMeO Hf GdhdjO Hf GdCRQbs ((3eMeO Hf SYjO Hf EHQGgje GdQGTOi GdMejOi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CWdY Ydi XdeGJ GdTQc ai CHQGL GdfHhAI TeS GdQSGdI CeG HYO (B: (3aEfi deG QCjJ LedI ef GdENhGf GdeQGHWjf eVWQjf Edi GdeYGedGJ fOHfi Pdc Edi JbjjO hJbSje CTQM ajg MGd GdeYGedI s
(3BNQgG (B:s
(3Pdc GdVYa ai Jdc GdShb bjd dg gPG cdg UMjM hbd HjffG Pdc ai cJGH GdTHgGJ HMhd Gddg GfJgi cdGeg hBNQ OYhGfG Cf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B1 - (3U(B109s
(3HBNQg JYbjH ef bGQF bGQf Hjf gPG GdcJGH hcJGH BNQs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B315s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1189/1) s
Keywords: (3Gdabg GdESdGejs